Pengaruh Media Sosial terhadap Penyakit ʻAin: Analisis Hadis dan Implikasinya bagi Kesehatan Mental Mahasiswa Ilmu Hadis UIN Sumatera Utara - Lubis, Jihan Aprilia; Is, Fadhilah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The phenomenon of social media as a modern interaction space has opened up vast opportunities for the dissemination of information, but on the other hand, it has also become a potential medium for the emergence of the disease of ʻain, namely disorders caused by hasad or jealous views accompanied by admiration, as mentioned in several hadith. Among students of Hadith Studies at UIN North Sumatra, excessive use of social media without spiritual control has the potential to open a gap for the negative influence of 'ain, which is not only spiritual but also has an impact on physical and psychological health. This study aims to examine the influence of social media on the disease of ʻain from the perspective of hadith and analyze its impact on student health. The research method used is qualitative with a descriptive-analytical approach, observation, interviews, and documentation as data collection techniques, as well as content analysis to interpret the meaning of texts and phenomena. The results show that students who tend to share personal achievements excessively on social media experience psychosomatic symptoms such as anxiety, sleep disorders, headaches, and intense feelings of anxiety, especially after receiving negative comments or excessive expressions of admiration from others. The Prophet’s hadiths demonstrate that evil is a reality capable of killing and harming, so its prevention through remembrance of God (dhikr), protective prayers (taʻāwwuż), and spiritual strengthening is strongly emphasized. In conclusion, using social media without spiritual awareness can increase the risk of evil, and efforts to foster religious guidance based on hadith on campus are needed to increase students' preventive and protective awareness.